"Aspettando Godot" e la cosmogonia teatrale di Carlo Quartucci - Berlangieri, Maria Grazia (Mimesis Journal, 2020)
The essay analyses the theatrical cosmogony of Carlo Quartucci and the Compagnia della Ripresa, built around the understanding of Samuel Beckett’s dramaturgy with a primary focus on Waiting for Godot (The three first performances, 1959 - Teatro Brancaccio, Compagnia universitaria Latino-Metronio; 1964 – Teatro Stabile di Genova, Compagnia del Teatro Studio; 1965 – Festival di S. Beckett, Prima Porta Roma, Compagnia della Ripresa – Teatro Mobile). Furthermore, with the aid of unpublished interviews with Carlo Quartucci and Carla Tatò, Cosimo Cinieri and Emiliano Tolve, this study digs deeper inside the lesser known influen- ces on Quartuccis’s poetic such as the study of texts on figure and form by the art historian Carlo Lodovico Ragghianti and the “conceptual” work in the studio with the photographer Lisetta Carmi and his ideal and posthumous relationship with conceptual artist Marcel Brodhears.